(untitled) (Experimental biology, 2015)
Sex proportion is the important indicator of interspecific and intraspecific relationships of nematodes and the adaptive strategies of parasites’ population. In the most explorated adult semi-populations of A.galli the part of males was approximately 1/3 (30-38%) independently on the quantity of A.galli and presence of other helminthes species. The small number of males was registered in semi-populations with old females what may be related with the earlier males’ death.In the cases of parasitizing near 200 or more exemplars of A.galli the part of males was high not always, and in the several semi-populations was decreased. With high levels of infection the optimization of energy load to the host’s organism was realized by the decreasing of sizes as males as females, but not by the increasing of the part of less energy-expenditure males. Keeping of considerable part of females – is the most optimal population strategy thank to which the advantage as in the fertility as in the diversity was reached. With the increasing of the males’ part more than 45-50% the fertility of adult semi-populations of nematodes will consequently decrease, but the advantage in the polymorphism will not be.